Respuesta :

Answer:

y = -29/19  and x = -44/19

Step-by-step explanation:

3x + 2y = -10    multiply by -2  ⇔    -6x -  4y = 20

2x - 5y = 3       multiply by 3   ⇔      6x - 15y = 9    

Add the two equation                             -19y = 29

                                                                       y =  -29/19

Use equation one and solve for x

3x + 2(-29/19) = -10

3x - 58/19 = -10

3x = -10 + 58/19

3x = -190/19 + 58/19

3x = (-190 + 58)/19

  3x = -132/19

    x =  - 132/ 19 ÷3                           [tex]\frac{-132}{19} (\frac{1}{3} ) = \frac{-44}{19}[/tex]

    x =  -44/19